2021
DOI: 10.3390/antiox10091351
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Specificity Phosphatase 1 (DUSP1) Has a Central Role in Redox Homeostasis and Inflammation in the Mouse Cochlea

Abstract: Stress-activated protein kinases (SAPK) are associated with sensorineural hearing loss (SNHL) of multiple etiologies. Their activity is tightly regulated by dual-specificity phosphatase 1 (DUSP1), whose loss of function leads to sustained SAPK activation. Dusp1 gene knockout in mice accelerates SNHL progression and triggers inflammation, redox imbalance and hair cell (HC) death. To better understand the link between inflammation and redox imbalance, we analyzed the cochlear transcriptome in Dusp1−/− mice. RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Studies have shown that DUSP1 plays an important role in regulation of apoptosis and inflammatory response 17 , 18 . In this study we examine whether BCG infection upregulates DUSP1 expression and whether DUSP1 is involved in BCG-induced apoptosis and inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that DUSP1 plays an important role in regulation of apoptosis and inflammatory response 17 , 18 . In this study we examine whether BCG infection upregulates DUSP1 expression and whether DUSP1 is involved in BCG-induced apoptosis and inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…BCG infection induces apoptosis in THP-1 cells and promotes the expression of DUSP1 and proin ammatory cytokines. Studies have shown that DUSP1 plays an important role in regulation of apoptosis and in ammatory response 13,14 . In this study we examine whether BCG infection upregulates DUSP1 expression and whether DUSP1 is involved in BCG-induced apoptosis and in ammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that DUSP1,among the 10 family members, plays a regulatory role in a variety of cellular responses, especially in inflammation. Prior reports have indicated that DUSP1 regulates oral cancer-associated inflammation and leukocyte infiltration ( 26 ). However, to date, the role of DUSP1 in muscle atrophy of cancer cachexia remains unclear.…”
Section: Discussionmentioning
confidence: 99%